Usability Testing of Industrial Engineering UPNVJT Website Using Eye Tracking and System Usability Scale - Bintara Putra Dicya; Tranggono (Politeknik Ganesha Medan, 2024)
Websites are essential for agencies and organizations to ensure their information is accessible to the public. The eye tracker method is effective for evaluating user usability. The Industrial Engineering Study Program at Universitas Pembangunan Nasional